A Meta-Analysis of the Relationship Between Organizational Citizenship Behavior and Employee Performance - Luthfiyana, Dzakiah Azizah; Widowati, Retno; Surwanti, Arni (Asian Journal of Management Analytics, 2024)
This paper aims to identify research trends on values and organizational citizenship behavior (OCB) and their effect on employee performance globally. The Method used in this study is qualitative research with literature review. As for the data found, 109 documents were obtained and analyzed 2014-2023. This dataset was converted to CSV format andfor Bibliometrix in the analysis using VOSviwer. The study included publication distribution year, country, keywords, and authors. This study's findings show that the research trend from 2014 to 2023 indexed by Scopus has increased. 2020 became the year with the highest number of research publications on Citizenship Organizational Behavior and Employee Performance. Indonesia was identified as the country that contributed the most to the publication of this research, with studies in Citizenship Organizational Behavior, Job Rotation, and Physical Work Environment. This paper reveals the research trends and areas of Citizenship, Organizational Behavior, and employee performance. The results help scholars quickly understand the research of Citizenship Organizational Behavior